Effectiveness Of Nursing Intervention and Community Initiatives To Preventing Childhood Obesity Among Mothers At Selected Areas At Agra, Uttarpradesh - Kurane, Swati Chandrahas; Nisha, Sumbul; Y. Oza, Namrataben; Mahammad, Suleman Shareef; Ambli.V, Ambli.V; Kavitha G, LtCol (Journal of Neonatal Surgery, 2025)
Background: Obesity among children and adolescents continues to rise worldwide. Despite the efforts of the healthcare workforce, limited high‐quality evidence has been put forward demonstrating effective childhood obesity interventions. The role of nurses as primary actors in the prevention of childhood obesity has also been under researched given the size of the workforce and their growing involvement in chronic disease prevention. Objective: To assess the effectiveness of nursing intervention to prevent childhood obesity. Methods: The study was conducted in selected community areas at uttarpradesh by two data collectors and selected community areas.50 obesity children’s mothers were selected and purposive sampling technique used to select samples. The questionnaire was checked for completeness, cleaned manually and entered into Epi- Data version 4.2. Then the data was transferred into SPSS version 21.0 for further analysis. Descriptive statistics were carried out. Finally checked association between dependent and independent variables. Results: Revealed that pretest and posttest level of knowledge regarding preventing childhood obesity among mother’s pretest level good knowledge 0.00 percent, average knowledge 20(40%) and poor knowledge 30(60%) and posttest level of knowledge regarding preventing childhood obesity among mothers’ good knowledge 40(80%),10(20%) were average knowledge and 0(0.0%) were poor knowledge. So, P<0.05 level at significant. There was a significant association between preventing childhood obesity among mothers and their demographic variables such as educational status of mothers. p<0.05 level. There was no Significant association between the demographical variables such as age, religion, resident area, occupational status, number of children, monthly income and source of information at p<0.05 level. Conclusion: Although their effectiveness has not yet been established, nurse interventions to prevent obesity are viable. With the right training, nurses could more effectively utilize current clinical and situational opportunities to support the fight against pediatrics obesity.